Microplastics in freshwater: A focus on the Russian inland waters - Frank, Yuliya A.; Ershova, Alexandra; Batasheva, Svetlana; Vorobiev, Egor D.; Rakhmatullina, Svetlana; Vorobiev, Danil S.; Fakhrullin, Rawil (Water, 2022)
The low production costs and useful properties of synthetic polymers have led to their ubiquitous use, from food packaging and household products to high-tech applications in medicine and electronics. Incomplete recycling of plastic materials results in an accumulation of plastic waste, which slowly degrades to produce tiny plastic particles, commonly known as “microplastics” (MPs). MPs can enter water bodies, but only recently the problem of MP pollution of sea and fresh waters has become clearly evident and received considerable attention. This paper critically reviews the accumulated data about the distribution of MPs in the freshwater ecosystems of Russia. The available data on MP abundance in the lakes and river systems of the Russian Federation are analyzed (including the large Lakes Baikal, Ladoga, Onego, Imandra and Teletskoe, and the Volga, Northern Dvina, Ob, and Yenisei Rivers within their tributaries) and compared with the data on freshwater MP contents in other countries. In Russia, the main sources of MP pollution for rivers and lakes are domestic wastewater, containing microfibers of synthetic textiles, fishing tackle, and plastic waste left on shores. Among the MPs detected in the surface waters and bottom sediments, polyethylene (PE), polypropylene (PP), and polyethylene terephthalate (PET) particles predominate. The most common types of MPs in the surface freshwaters are fibers and fragments, with fibers prevailing in the bottom sediments. The reported average MP concentrations in the waters range from 0.007 items/m3 at the mouth of the Northern Dvina River to 11,000 items/m3 in the Altai lakes. However, the estimates obtained in different studies must be compared with great precaution because of significant differences in the methods used for MP quantification. The approaches to further improve the relevance of research into MP pollution of fresh waters are suggested.